NEGOTIATING MINANGKABAU CULTURAL IDENTITY IN POSTGRADUATE THESIS WRITING - Firdaus, Saiyidinal (ELite Journal : International Journal of Education, Language and Literature, 2026)
This study investigates the negotiation of Minangkabau cultural identity in postgraduate thesis writing through the perspectives of academic literacy, cultural discourse, and genre studies. In multilingual academic contexts, thesis writing functions not only as a disciplinary requirement but also as a site where writers reconcile local cultural values with global academic conventions. Despite growing research on writer identity, limited attention has been given to how Indonesian local epistemologies shape postgraduate genres. Adopting an interpretivist–critical paradigm, the study integrates Systemic Functional Linguistics (SFL), Critical Literacy, and Genre Pedagogy within a qualitative design. Data were collected from selected thesis chapters and semi-structured interviews with Minangkabau postgraduate students and supervisors in West Sumatra. Analysis combined metafunctional linguistic examination, genre move analysis, and critical discourse interpretation. The findings reveal that identity negotiation occurs ideationally through the transformation of cultural philosophy into academic knowledge, interpersonally through culturally informed stance and politeness strategies, and textually through hybrid genre structures that merge institutional conventions with local narratives. These practices illustrate students’ agency in reshaping academic discourse while maintaining cultural authenticity. The study argues that postgraduate academic writing should be viewed as a culturally situated practice and recommends culturally responsive genre pedagogy that acknowledges diverse epistemologies within Indonesian higher education.